Principles of Flexible Endoscopy for Surgeons - Marks, Jeffrey M.; Dunkin, Brian J. (Springer New York : Imprint: Springer, 2013)
Written entirely by surgical endoscopists, Principles of Flexible Endoscopy for Surgeons presents a comprehensive overview of past, present, and future flexible gastrointestinal endoscopic techniques, with a focus on educating surgeons who may or may not already have the skills to perform flexible endoscopy. In addition to the endoscopic management of surgical issues, the volume describes the role of surgery in the management of endoscopic complications. Basic as well as advanced flexible endoscopic techniques are presented in both a didactic and visual mode, with representative endoscopic images and video clips. Recent endoscopic advancements which are not routinely a core component of surgical training programs are also covered in detail. Extensively illustrated with endoscopic images and accompanied by a DVD, Principles of Flexible Endoscopy for Surgeons is a valuable resource for surgeons on all facets of flexible endoscopy.